Implementation of Online Learning in Aqidah Akhlak Lessons - Melyani Sari Sitepu; Muhammad Anas Maarif; Abd Basir; Aslan Aslan; Angga Pranata (AL-ISHLAH: Jurnal Pendidikan, 2022)
This article aims to identify and describe the planning, implementation, and evaluation of online learning on Aqidah Akhlak subjects at a Madrasah Tsanawiyah in Palembang. This article uses a type of qualitative research with a case study approach. Researchers' data collection techniques are by conducting participant observation, documentation, and interviews. This study's data sources include the vice-chairman of the madrasa curriculum, teaching teachers of moral aqidah subjects, and several students involved in research on online learning of moral aqidah subjects. The results of the discussion of this article are 1) Online learning planning using the 2013 curriculum and preparing lesson plans (RPP) with online designs. 2) Implementation of online learning, educators emphasise using exciting learning media such as video displays and power points related to learning materials. There are sharing activities carried out after learning takes place, 3) Evaluation of online learning is carried out based on taking daily test scores, semester exams, and assessment of the cognitive, affective, and psychomotor domains.